Biophysical characterization of full‐length TAR DNA‐binding protein (TDP‐43) phase separation. (28th November 2022) - Staderini, Tommaso; Bigi, Alessandra; Mongiello, Daniele; Cecchi, Cristina; Chiti, Fabrizio
Abstract: Amyotrophic lateral sclerosis and frontotemporal lobar degeneration with ubiquitin‐positive inclusions are associated with deposition of cytosolic inclusion bodies of TAR DNA‐binding protein 43 (TDP‐43) in brain and motor neurons. We induced phase separation of purified full‐length TDP‐43 devoid of large tags using a solution‐jump method, and monitored it with an array of biophysical techniques. The tetramethylrhodamine‐5‐maleimide‐ or Alexa488‐labeled protein formed rapidly (<1 min) apparently round, homogeneous and 0.5–1.0 μm wide assemblies, when imaged using confocal fluorescence, bright‐field, and stimulated emission depletion microscopy. The assemblies, however, had limited internal diffusion, as assessed with fluorescence recovery after photobleaching, and did not coalesce, but rather clustered into irregular bunches, unlike those formed by the C‐terminal domain. They were enriched with α‐helical structure, with minor contributions of β‐sheet/random structure, had a red‐shifted tryptophan fluorescence and did not bind thioflavin T. By monitoring with turbidimetry both the formation of the spherical species and their further clustering under different experimental conditions, we carried out a multiparametric analysis of the two phenomena. In particular, both processes were found to be promoted by high protein concentrations, salts, crowding agents, weakly by reducing agents, as the pH approached a value of 6.0 from either side (corresponding to the TDP‐43 isoionic point), and as the temperature approached a value of 31°C from either side. Important differences were found with respect to the TDP‐43 C‐terminal domain. Our multiparametric results also provide explanations to some of the solubility data obtained on full‐length TDP‐43 that were difficult to explain following the multiparametric analysis acquired on the C‐terminal domain.